Use of The Services of Transwests As Bridal Make-Up According To Dsn Mui Fatwa No. 112/Dsn-Mui/Ix/2017 (Case Study of Mompang Julu Village, Mandailing Natal District) - Indah Sukriah Btr; Rahmad Efendi (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2023)
We must do our work in accordance with the Sharia, while the people of Mompang Julu still use the services of transvestites. Even though all the people of Mompang Julu are Muslims, they still ignore and consider it normal for transvestites as bridesmaids to make up because they only prioritise beauty for a moment without caring about who does it. do their make-up without any more restrictions in front of transvestites who are clearly male transvestites.Â Waria has taken over all the make-up artists in Mompang Julu village, causing this influence. This research aims to find out the law regarding the use of transgender services as bridesmaids from the perspective of DSN MUI Fatwa No. 112/DSN-MUI/IX/2017. The method in this research uses an empirical type of juridical law with a living case study approach. Field data was collected through observation and interviews; the data obtained was processed using qualitative methods and analysed based on the logic of deductive thinking related to research studied by DSN MUI Fatwa No. 112/DSN-MUI/IX/2017. The results of this research show that people still do not understand Islamic law regarding transgender women as bridesmaids because local people only prioritise appearance at weddings rather than Islamic rules. MUI Fatwa No. 112/DSN-MUI/IX/2017 and Article 1230 of the Criminal Code prohibit and invalidate their services as they violate Islamic rules.